ANALISIS DETERMINAN PENYERAPAN ANGGARAN PADA PEMERINTAH DAERAH KABUPATEN OGAN KOMERING ILIR - Meutia Gunawan; Muhammad Husni Mubarok; Yuli Antina Aryani (Jurnal Akuntansi dan Bisnis (AKUNTANSI), 2026)
The purpose of this study was to evaluate the level of budget planning, budget implementation, human resource quality, and the procurement process influence budget absorption within the Regional Government of Ogan Komering Ilir Regency. A quantitative research approach was employed, utilizing primary data collected through structured questionnaires. The study involved 105 respondents representing 35 local government agencies, selected through a purposive sampling technique. Data analysis procedures included instrument testing multiple linear regression analysis, descriptive statistics, traditional assumption tests, validity and reliability checks, and hypothesis testing are all used in this work. Although budget planning, budget implementation, and human resource quality all significantly and favourably affect budget realisation, the data show that the acquisition of products, the acquisition of goods and services has no discernible impact. All things considered, these four elements have a major impact on how well local governments absorb their budgets.